2021
DOI: 10.1108/bepam-09-2021-0113
|View full text |Cite
|
Sign up to set email alerts
|

Causes of road projects' delays: a case of Blantyre, Malawi

Abstract: PurposeThe study aims to find the causes of road projects implementation delays in Blantyre, one of the four city councils (CCs) in Malawi.Design/methodology/approachThe study followed a qualitative research approach using a Blantyre City Council (BCC) as a case study. This study combined in-depth, face-to-face interviews with councillors, secretariat staff, consultants, and contractors who worked on the city's road projects. Data gathered were analysed using thematic content analysis. Also, some road project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Likewise, the government's inability to properly acquire the land earmarked for the project from the traditional leaders led to site ownership issues when the project was about to commence. These issues were also identified by Mwamvani et al [46], where road infrastructure projects in Malawi needed to be completed due to project site issues.…”
Section: P6: "Capital Availability Price Inflation Of Materials Scarc...mentioning
confidence: 95%
“…Likewise, the government's inability to properly acquire the land earmarked for the project from the traditional leaders led to site ownership issues when the project was about to commence. These issues were also identified by Mwamvani et al [46], where road infrastructure projects in Malawi needed to be completed due to project site issues.…”
Section: P6: "Capital Availability Price Inflation Of Materials Scarc...mentioning
confidence: 95%
“…The study on both public and private construction projects enhanced the significance of the study. Although Mwamvani, Amoah [ 36 ] ’s quantitative study suggested methods for construction project delays, it was limited to a single organisation in Malawi, hence the findings could not be generalised.…”
Section: Introductionmentioning
confidence: 99%